REACtiVe-2 : phase I evaluation of dendritic cell vaccination and agonistic CD40 therapy following (m)FOLFIRINOX in metastatic pancreatic cancer - Kucukcelebi, Songul; van 't Land, Freek R; van der Burg, Sjoerd H; Eskens, Ferry A L M; Homs, Marjolein Y V; Willemsen, Marcella; Onrust-van Schoonhoven, Anne; Rozendaal, Nina E M; Fellah, Amine; Vadgama, Disha; Moskie, Miranda; Bezemer, Koen; et al. (Nature Communications, 2025)
In pancreatic ductal adenocarcinoma (PDAC), the dense desmoplastic stroma and insufficient infiltrating T cells represent a significant barrier to effective immunotherapy. In this phase I, dose-escalation study, previously registered at the Dutch Trial Register and later on at ClinicalTrial (NCT05650918), we administer an autologous dendritic cell (DC) vaccine (MesoPher) with an agonistic CD40-specific antibody (mitazalimab) to metastatic PDAC patients (n = 16) after (m)FOLFIRINOX treatment. We included patients with WHO performance status 0-1 with accessible metastatic lesions, and excluded patients with history of previous immunotherapy or malignant ascites. Primary objectives include safety and tolerability. Immune modulation and clinical outcomes are monitored as secondary objectives. MesoPher (25 × 10 6 DCs) is co-administered with 300, 600, or 1200 μg/kg mitazalimab. MesoPher/mitazalimab therapy is safe and well-tolerated, and the primary endpoint is met. One transient dose-limiting toxicity (DLT) is observed (grade 3 fever). MesoPher/mitazalimab induces a systemic increase in activated and vaccine-specific T cell responses. In post-therapy tumor biopsies, increased T cell infiltration and decreased collagen deposition are observed. No objective radiological response is observed, but eight patients (50%) show stable disease after three administrations. In conclusion, MesoPher/mitazalimab combination therapy is safe and tolerable in patients with metastatic PDAC and enhances systemic immune activation and local immune responses. Future research should evaluate the efficacy of this promising approach as maintenance therapy shortly after completing chemotherapy.
© 2025. The Author(s).
Keywords: Humans; Pancreatic Neoplasms/therapy; Dendritic Cells/immunology; Male; Cancer Vaccines/immunology; Middle Aged; Female; Aged; CD40 Antigens/agonists; Carcinoma, Pancreatic Ductal/therapy; Vaccination; Adult; Antineoplastic Combined Chemotherapy Protocols/therapeutic use; Treatment Outcome; Neoplasm Metastasis; Immunotherapy/methods